Copper Nanoparticles Induced Genotoxicty, Oxidative Stress, and Changes in Superoxide Dismutase (SOD) Gene Expression in Cucumber (Cucumis sativus) Plants - Mosa, Kareem A.; El-Naggar, Mohamed; Ramamoorthy, Kalidoss; Alawadhi, Hussain; Elnaggar, Attiat; Wartanian, Sylvie; Ibrahim, Emy; Hani, Hala (Frontiers in Plant Science, 2018)
Abstract With the increased use of metal nanoparticles, their access to the food chain has become a main concern to scientists and holds controversial social implications. This research particularly sheds light on copper nanoparticles (CuNP), as they have been commonly used in several industries nowadays. In this study, we investigated the phytotoxicity of CuNP on cucumber (Cucumis sativus) plants grown hydroponically. Atomic Absorption Spectroscopy (AAS), X-Ray Fluorescence (XRF) and Scanning Electron Microscopy (SEM) analysis confirmed that C. sativus treated with CuNP accumulated CuNP in the plant tissues, with higher levels in roots, with amounts that were concentration dependent. Furthermore, genotoxicity was assessed using Random Amplified Polymorphism DNA (RAPD) technique, and our results showed that CuNP caused genomic alterations in C. sativus. To the authors’ knowledge, this is the first report of the genotoxic potential of CuNP in cucumber plant. Phenotypical, physiological, and biochemical changes were assessed by determining the CuNP treated plant’s total biomass, chlorophyll, H2O2 and MDA contents, and electrolyte leakage percentage. The results revealed notable adverse phenotypical changes along with decreased biomass and decreased levels of the photosynthetic pigments (Chlorophyll a and b) in a concentration-dependent manner. Moreover, CuNP induced damage to the root plasma membrane as determined by the increased electrolyte leakage. A significant increase in H2O2 and MDA contents were detected in C. sativus CuNP treated plants. Additionally, superoxide dismutase (Cu-Zn SOD) gene expression was induced under CuNP treatment. Overall, our results demonstrated that CuNP of 10 - 30 nm size were toxic to C. sativus plants. This finding will encourage the safe production and disposal NPs. Thus, reducing nano-metallic bioaccumulation into our food chain through crop plants; that possesses a threat to the ecological system.